A heavy-ion production channel of 149Tb via 63Cu bombardment of 89Y. (December 2021) - Wilkinson, John T.; Barrett, Kendall E.; Ferran, Samuel J.; McGuinness, Sean R.; McIntosh, Lauren A.; McCarthy, Mallory; Yennello, Sherry J.; Engle, Jonathan W.; Lapi, Suzanne E.; Peaslee, Graham F.
Abstract: The radionuclide 149 Tb ( t 1/2  = 4.1 h) is a potential theranostic isotope which can simultaneously be used for targeted-alpha-particle therapy and positron-emission tomography. Feasibility experiments were performed to test a near-symmetric heavy-ion reaction of 63 Cu bombardment on monoisotopic 89 Y. The indirect reaction was studied to avoid isomer production. Offline gamma spectroscopy was used to quantify thick-target physical yields and experimental results show modest agreement to the fusion-evaporation code PACE4. A near-symmetric fission yield was also observed. Highlights: Indirect heavy-ion reactions were investigated for the production of 149 Tb. Gamma spectroscopy was used to quantify thick-target physical yields. PACE4 fusion-evaporation predictions show modest agreement to experimental results. A near-symmetric fission yield was observed for the compound nucleus 152 Er.